The Effect of Discounts, Brands, and Marketing Strategies on Customer Loyalty of Daihatsu Oil PT. Nusantara Autopart Persada - Nyosino; Brilian Moktar; Budijanto (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This study aims to determine the effect of Discount on Customer Loyalty at PT. Nusantara Autopart Persada, determine the effect of Brand on Customer Loyalty at PT. Nusantara Autopart Persada, determine the effect of Marketing Strategy on Customer Loyalty at PT. Nusantara Autopart Persada, determine the effect of Discount, Brand and Marketing Strategy on Customer Loyalty at PT. Nusantara Autopart Persada. The population in this study are customers of PT. Nusantara Autopart Persada totaling 148 respondents. The technique of determining the number of samples used in this study is Slovin formula and totaling 108 respondents. The results of the research analysis show that Discount, Brand and Marketing Strategy partially have a positive and significant effect on Customer Loyalty at PT. Nusantara Autopart Persada. The results showed that Discount, Brand and Marketing Strategy simultaneously have a positive and significant effect on Customer Loyalty at PT. Nusantara Autopart Persada. The results of this study are supported by the value of R square (R2) which means Discount, Brand and Marketing Strategy have an effect on Customer Loyalty at PT. Nusantara Autopart Persada. While the remaining is effected by other factors originating from outside this research model such as location, distribution, and sales promotion.